Fiscal Regulatory Frameworks through the National Revenue Authority as an Engine of Economic Growth in Sierra Leone: An Overview - Hassan Elsan Mansaray (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The study explored the fiscal regulatory frameworks through the NRA as an engine of economic growth in Sierra Leone. The study revealed that revenue mobilization is an important device for the Government of Sierra Leone (GoSL) in accomplishing its determinations for poverty reduction; delivering its Agenda for Prosperity; building up financial independence; and reaching middle income standing. It also exposed that the financial and regulatory frameworks that support NRA to perform effective revenue mobilization are based on the following regulations and laws such as: revenue laws enacted by parliament; annual budget, Finance Act, Strategic plan; the assessment of collection and accounting for all revenue collected. In addition, the use of electronical based systems, the provision of tax legislation and policy, transparency in the tax administration, modernization of custom service department, the national acts, regional treaties, other international treaties are some of the financial and regulatory frameworks that back NRA to perform effective revenue mobilization.